The Middle East amid Global Multipolarity: The Emergence of New Actors in the Region involving the BRICS Countries - Mohammed, Yasmin (InterAção, 2015)
Political instability and riots happening in many Arab countries coincided with the expansion of BRICS. These five countries are among the most powerful countries in the international arena and their opinions are of paramount importance since all members of the Security Council of the United Nations, China and Russia are permanent members and Brazil, India and Africa South are not permanent members, but are seeking permanent representation for greater influence in the world. The ongoing reorganization of the political landscape in the Middle East and North Africa opened new space for the BRICS to the international prestige on responding to this turmoil. The big changes are now being caused not by victories on the battlefield or new geopolitical alignments, but by a single factor in our modern world - rapid economic growth, which will profoundly impact the International Relations and International Security.